Genetic heterogeneity of Meckel syndrome. Issue 12 (December 1997) - Roume, J; Ma, H W; Le Merrer, M; Cormier-Daire, V; Girlich, D; Genin, E; Munnich, A
Abstract : Meckel syndrome (MKS) is a lethal, autosomal recessive condition characterised by an occipital meningoencephalocele, enlarged kidneys with multicystic dysplasia, fibrotic changes of the liver in the portal area with ductal proliferation, and postaxial polydactyly. Recently, a MKS gene has been mapped to chromosome 17q21-q24 in Finnish families, with no evidence of locus heterogeneity in this population. Here, we report the exclusion of chromosome 17q21-q24 in eight typical MKS families of North African and Middle Eastern ancestry and provide evidence for genetic heterogeneity of this condition.